SMALL BUSINESS ENTREPRENEURSHIP IN VIETNAM: THE CASE OF THE PUBLIC RELATIONS INDUSTRY [USAHA KECIL DI VIETNAM: KASUS PUBLIC RELATIONS INDUSTRI] - Tuong-Minh Ly-Le (DeReMa (Development Research of Management): Jurnal Manajemen, 2021)
A better understanding of entrepreneurship in different sectors and its motivations, roles, and challenges offer new opportunities for entrepreneurs to start their business and participate in the national and global economy. This research studied the different entrepreneurial factors that influence the growth stage of public relations companies in Vietnam. In particular, the research examined how the founder's role shifted during the growth stage, and the motivations behind the founder's decision to retain or release their control in this stage. Using the inductive, grounded theory approach to explore the decision of a founder in Vietnam’s public relations industry during a company’s growth stage, this study found that public relations founders in Vietnam are generally driven by the accomplishments and challenges picked up from their entrepreneurial journey. Their journey mainly revolves around managerial experience, as the managerial tasks would be more complicated and require better managerial skills to address the challenges. They are also open to delegating their role to a professional manager, who already possesses the required management skills, to support the business.Abstrak dalam Bahasa Indonesia. Pemahaman yang lebih baik tentang kewirausahaan di berbagai sektor dan motivasi, peran, dan tantangannya menawarkan peluang baru bagi pengusaha untuk memulai bisnis mereka dan berpartisipasi dalam pembangunan ekonomi nasional dan global. Penelitian ini mempelajari faktor-faktor kewirausahaan yang mempengaruhi tahap pertumbuhan perusahaan Public Relation di Vietnam. Secara khusus, penelitian ini meneliti bagaimana bergesernya peran pendiri dalam beberapa tahap pertumbuhan, dan motivasi di balik keputusan pendiri untuk mempertahankan atau melepaskan pengaruh mereka pada tahap tertentu. Penelitian ini menggunakan pendekatan induktif, grounded theory untuk mengeksplorasi keputusan seorang pendiri pada industri Public Relation di Vietnam selama tahap pertumbuhan perusahaan, penelitian ini menemukan bahwa pendiri umumnya didorong oleh pencapaian dan tantangan yang diambil dari perjalanan kewirausahaan mereka. Perjalanan mereka terutama berkisar pada pengalaman manajerial,Tugas manajerial akan lebih rumit dan membutuhkan keterampilan manajerial yang lebih baik untuk mengatasi tantangan. Mereka juga terbuka untuk mendelegasikan peran mereka kepada manajer profesional, yang telah memiliki keterampilan manajemen yang dibutuhkan, untuk mendukung bisnis.